Language Games on Social Media: A Wittgenstein Analysis of Youth Identity Formation and Social Relations - Agustinus Abraham (STAI YPIQ BAUBAU, SULAWESI TENGGARA, 2026)
The rapid development of digital technology has transformed patterns of communication and social interaction, particularly through the widespread use of social media platforms. This study examines how language practices on social media shape youth identity formation and social relations through the philosophical perspective of Ludwig Wittgenstein’s concept of language games. Using a qualitative method with a literature review approach, the study analyzes various academic sources to interpret digital linguistic practices among young people. The findings indicate that language on social media functions not merely as a medium for transmitting information but as a social practice governed by specific rules, conventions, and contexts of use. Expressions such as emojis, memes, slang, hashtags, and other symbolic forms operate as elements of language games that enable young users to construct and display their identities, build group solidarity, and negotiate social meanings within digital communities. At the same time, these linguistic practices also reveal tensions between honesty and manipulation, as reflected in phenomena such as false self-presentation, hoaxes, and persuasive language strategies. Therefore, social media language both reflects and actively shapes contemporary social realities, influencing how individuals understand themselves, others, and the dynamics of meaning and power in digital communication.